Geospatial Visualization of Estates Rental Using Google Maps - Khalifa, Salem S. M. (2010)
Location is the main important thing for an accommodation-seeker who is looking for a place for rent or to buy a property. Searching for rental accommodation can be a difficult and frustrating process. Many hours or days must be spent searching through numerous disparate sources of property advertisements in order to locate suitable candidates. This problem mostly facing the international students in Malaysia when they are searching for rental accommodation. Researcher aim to provide just such support with GVERGM system for rental property recommendation using Google Maps to solve this problem, currently focused on international students in Malaysia.